DETERMINATION OF THE SUBSTANCES THAT GETTING TO THE ENVIRONMENT IN THE PLACES OF THE PROCESSING OF THE ELECTRONIC WASTES. PART 2. ORGANIC COMPOUNDS: UDC 614.7, 628.5 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2009)
The GC/MS identification of organic compounds was performed on the environmental samples which have been affected by the processing of electronic wastes in China and India. The main groups of anthropogenic organic compounds, which were found in the samples of dust, soil and sediments, were represented by the classes of halogenated compounds including polychlorinated biphenyls, polychlorinated benzenes, polybrominated diphenyl ethers and chlorinated pesticides. Some samples also contained brominated benzenes, polychlorinated naphthalenes, polycyclic siloxanes, phthalate esters and organophosphorus compounds.
Keywords: -